Review of the Belt and Road Initiative within the First Decade and Future Research Suggestions - Yang, Mei; Abd Hamid, Hamizah; Lai, JingTing (International Journal of Economics and Management, 2026)
This study categorizes the themes and sub-themes of the articles discussing the Belt and Road Initiative (B&R) through international business perspective, to explore the research trends of B&R in the international business field. Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to review the literature on the topic published from 2013-2023, clustered the research content using VOSviewer to identify the topics and keywords of existing research in this field. 104 articles were reviewed and analyzed, revealing three main themes which are regional cooperation, OFDI, and infrastructure development. This study also provides suggestions for future research. The article provides suggestions for researchers investigating topics relating to B&R, by clarifying the main themes for the topic and providing suggestions for future research. For practitioners, this study can assist in making decisions and improve by case comparation, theoretical analysis, and model reference.